2016
DOI: 10.18632/oncotarget.12364
|View full text |Cite
|
Sign up to set email alerts
|

Advanced lung adenocarcinomas with ROS1-rearrangement frequently show hepatoid cell

Abstract: Defining distinctive histologic characteristics of ROS1-rearranged non-small-cell lung carcinomas (NSCLCs) may help identify cases that merit molecular testing. However, the majority of previous reports have focused on surgical specimens but only limited studies assessed histomorphology of advanced NSCLCs. In order to identify the clinical and histological characteristics of ROS1-rearranged advanced NSCLCs, we examined five hundred sixteen Chinese patients with advanced NSCLCs using ROS1 fluorescence in situ h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…238,239,249 While ROS1-rearranged NSCLC is similar to ALK-rearranged NSCLC in that it is associated with a younger age at presentation (median: 49.8 years) and adenocarcinoma histology, significant associations do not hold for smoking, especially in Asian cohorts, and indoor radon gas exposure has been identified as a primary risk factor in nonsmokers. 238,[249][250][251] In terms of histology, ROS1 signet-ring cells are also prevalent in Western populations while in an evaluation of over 500 Chinese patients with advanced NSCLC, 11 of 16 (68.8%) ROS1 fusion-positive tumors had hepatoid cytology or cribriform structure. 249,250 Overall, prognosis with ROS1 is favorable with 40% alive at 4 years without targeted therapy and 60% alive with targeted therapy.…”
Section: Ros1 Fusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…238,239,249 While ROS1-rearranged NSCLC is similar to ALK-rearranged NSCLC in that it is associated with a younger age at presentation (median: 49.8 years) and adenocarcinoma histology, significant associations do not hold for smoking, especially in Asian cohorts, and indoor radon gas exposure has been identified as a primary risk factor in nonsmokers. 238,[249][250][251] In terms of histology, ROS1 signet-ring cells are also prevalent in Western populations while in an evaluation of over 500 Chinese patients with advanced NSCLC, 11 of 16 (68.8%) ROS1 fusion-positive tumors had hepatoid cytology or cribriform structure. 249,250 Overall, prognosis with ROS1 is favorable with 40% alive at 4 years without targeted therapy and 60% alive with targeted therapy.…”
Section: Ros1 Fusionsmentioning
confidence: 99%
“…238,[249][250][251] In terms of histology, ROS1 signet-ring cells are also prevalent in Western populations while in an evaluation of over 500 Chinese patients with advanced NSCLC, 11 of 16 (68.8%) ROS1 fusion-positive tumors had hepatoid cytology or cribriform structure. 249,250 Overall, prognosis with ROS1 is favorable with 40% alive at 4 years without targeted therapy and 60% alive with targeted therapy. 249…”
Section: Ros1 Fusionsmentioning
confidence: 99%
“…These patients are predominantly young women and never‐smokers . In addition to the morphologic features of fusion‐positive ALK lung adenocarcinomas (extracellular mucin, cribriform pattern, and signet ring cells), ROS1 ‐positive tumors exhibit hepatoid cytology (abundant eosinophilic cytoplasm, round and relatively monomorphic nuclei, and prominent nucleoli) . Crizotinib, which induced an impressive dramatic objective clinical response in 72% of ROS1 ‐positive patients with advanced‐stage NSCLC, recently was approved by the FDA also for ROS1 ‐rearranged adenocarcinomas.…”
Section: Ros1mentioning
confidence: 99%
“…73 In addition to the morphologic features of fusion-positive ALK lung adenocarcinomas (extracellular mucin, cribriform pattern, and signet ring cells), 14 ROS1-positive tumors exhibit hepatoid cytology (abundant eosinophilic cytoplasm, round and relatively monomorphic nuclei, and prominent nucleoli). 74 Crizotinib, which induced an impressive dramatic objective clinical response in 72% of ROS1-positive patients with advanced-stage NSCLC, 9 recently was approved by the FDA also for ROS1-rearranged adenocarcinomas. In the clinical trials with crizotinib, ROS1-positive patients were identified by break-apart FISH; consequently, the FDA considers this method to be the "gold standard" procedure with which to determine ROS1 positivity.…”
Section: Ros1mentioning
confidence: 99%
“…A retrospective analysis of 48 lung adenocarcinoma cases reported that presence of flat mono‐layered sheets and acini, mild nuclear atypia, fine chromatin and smooth nuclear margins are important predictors of EGFR mutated status . Similarly, another study showed that the presence of a solid pattern on histology with hepatoid cytology or acinar pattern with cribriform structure along with abundant extracellular mucus or signet‐ring cells are independent predictors of ROS1‐rearranged advanced lung cancer . Due to lack of uniformity in parameters evaluated and possible overlapping features, there is a need to define a standardised set of cytomorphological parameters that could clearly differentiate among the three types of mutated adenocarcinoma.…”
mentioning
confidence: 99%